2018
DOI: 10.1101/320432
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Robust associative learning is sufficient to explain structural and dynamical properties of local cortical circuits

Abstract: The ability of neural networks to associate successive states of network activity lies at the basis of many cognitive functions. Hence, we hypothesized that many ubiquitous structural and dynamical properties of local cortical networks result from associative learning. To test this hypothesis, we trained recurrent networks of excitatory and inhibitory neurons on memory sequences of varying lengths and compared network properties to those observed experimentally. We show that when the network is robustly loaded… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(38 citation statements)
references
References 43 publications
6
32
0
Order By: Relevance
“…On one hand, (a) there exist independent empirical evidences that excitatory to pairs is overexpressedcompared to random network -in rat's visual (Song et al, 2005) and somatosensory (Perin et al, 2011) cortex. In a recent theoretical study this overexpression is explained as a consequence of maximizing capacity of the associative memory (Zhang et al, 2019); these suggest that the emergence of excitatory to pairs is not an accidental observation. On the other hand, (b) we have shown that whenever the background network is sparse, strong negative triple-wise is the signature of excitatory to pairs; and even simultaneous presence of excitation and inhibition does not disturb this conclusion.…”
Section: Discussionmentioning
confidence: 93%
“…On one hand, (a) there exist independent empirical evidences that excitatory to pairs is overexpressedcompared to random network -in rat's visual (Song et al, 2005) and somatosensory (Perin et al, 2011) cortex. In a recent theoretical study this overexpression is explained as a consequence of maximizing capacity of the associative memory (Zhang et al, 2019); these suggest that the emergence of excitatory to pairs is not an accidental observation. On the other hand, (b) we have shown that whenever the background network is sparse, strong negative triple-wise is the signature of excitatory to pairs; and even simultaneous presence of excitation and inhibition does not disturb this conclusion.…”
Section: Discussionmentioning
confidence: 93%
“…Second, as synaptic connectivity of neurons changes during learning (3), it is not unreasonable to expect that the requirement of reliable memory retrieval is reflected in the properties of network connectivity and, consequently, the activity of neurons in the brain. Interestingly, local neural networks in the mammalian cortical areas have many common features of connectivity and network activity (18). We show that these network properties in the model emerge all at once during reliable memory storage.…”
Section: Introductionmentioning
confidence: 80%
“…The replica method (32,33) provides an analytical solution in the N → ∞ limit. Though neuron networks in the brain are finite, they are thought to be large enough to have many properties that are well described by this limit (18). More importantly, the analytical solution of the replica method reveals the dependence of the results on combinations of network parameters that can be explored with other methods.…”
Section: B Solutions Of the Modelmentioning
confidence: 99%
See 2 more Smart Citations